2021
DOI: 10.1039/d1ta06568h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the cobalt content in cobalt iron oxides on the electrocatalytic OER activity

Abstract: Sub 10 nm cobalt ferrite CoxFe3-xO4 (x ≤ 1.75) nanoparticles and cobalt-rich wustite (Cox/3Fe(1-x)/3)O nanoparticles (x ≥ 2) were synthesized in a solvothermal approach and characterized by powder X-ray diffraction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 70 publications
5
59
1
Order By: Relevance
“…In an inverse spinel, half of the B 3+ cations occupy all tetrahedral sites and the remaining B 3+ and A 2+ are in octahedral sites, with Fe 3 O 4 in the form of magnetite being a prominent example. Therefore, the cation substitution of Co with Fe is appealing as it does not only change the chemical composition but also changes the degree of inversion and the magnetic properties. ,, Within one chemical composition, the cation site occupation in the O sub-lattice is prone to variations. , Recently, we showed that this occupation transforms dynamically in response to an anodic potential in spinel-like Co X Fe 3 –X O Y nanoparticles . Co- and Fe-based spinel oxides are widely regarded as affordable and stable anode materials and are being considered for industrial applications, with low reported overpotentials. , The stability of the spinel crystal structure has been underlined by a study of Co 3 O 4 films, which reversibly form amorphous CoO X (OH) Y with more pronounced di-μ-oxo-bridged Co ions under OER conditions but recrystallize to the initial spinel structure after the reaction .…”
Section: Introductionmentioning
confidence: 99%
“…In an inverse spinel, half of the B 3+ cations occupy all tetrahedral sites and the remaining B 3+ and A 2+ are in octahedral sites, with Fe 3 O 4 in the form of magnetite being a prominent example. Therefore, the cation substitution of Co with Fe is appealing as it does not only change the chemical composition but also changes the degree of inversion and the magnetic properties. ,, Within one chemical composition, the cation site occupation in the O sub-lattice is prone to variations. , Recently, we showed that this occupation transforms dynamically in response to an anodic potential in spinel-like Co X Fe 3 –X O Y nanoparticles . Co- and Fe-based spinel oxides are widely regarded as affordable and stable anode materials and are being considered for industrial applications, with low reported overpotentials. , The stability of the spinel crystal structure has been underlined by a study of Co 3 O 4 films, which reversibly form amorphous CoO X (OH) Y with more pronounced di-μ-oxo-bridged Co ions under OER conditions but recrystallize to the initial spinel structure after the reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Co oxides with a spinel structure generally exhibit good OER properties (Bergmann et al, 2015;Chen et al, 2015;Xu et al, 2019). Saddeler et al describes the effect of adding Co to Fe 3 O 4 , which comes into play in HESp3, where Co improves OER reaction kinetics (Saddeler et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the existing studies, it has been proposed that the surface reconstruction of the catalyst is an important reason for the performance improvement so we have characterized sample 500 after catalysis. 38 Fig. 5a is a high-resolution plot of sample 500 after a long durability test, which shows that an amorphous layer with a thickness of about a few nanometers was produced on the surface of the catalyst.…”
Section: Resultsmentioning
confidence: 99%